2020
DOI: 10.1108/jmhtep-01-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Australian exercise physiology student attitudes and knowledge towards people living with mental illness

Abstract: Purpose Physical activity is increasingly recognised as critical to improving physical and mental health (MH). Understanding the education and training requirements of exercise professionals will support better integration of these emerging MH professionals within the multidisciplinary MH team. The purpose of this study was to determine the exposure to, knowledge and attitudes of final year exercise physiology students towards peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Overall scores and separate knowledge and attitude scores were obtained by summing the number of correct responses. Participants were categorised as having a "good" level of knowledge about mental health if their score was !50% (Chow et al, 2018;Fibbins et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Overall scores and separate knowledge and attitude scores were obtained by summing the number of correct responses. Participants were categorised as having a "good" level of knowledge about mental health if their score was !50% (Chow et al, 2018;Fibbins et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…With an increasing number of EPs and dietitians being embedded within multidisciplinary mental health-care teams, there is a need to ensure university programs are adequately preparing students to have the confidence to work with people with mental illness. A cross-sectional study of students completing their final year of an exercise physiology degree at a single university in Australia found that student knowledge of the treatment and lifestyle behaviours of people with mental illness was adequate: 68% of students scored 50% correct for knowledge questions (Fibbins et al, 2020), though the confidence levels remain unclear.…”
Section: Introductionmentioning
confidence: 99%